ANALISIS PENILAIAN KINERJA BERBASIS KEY PERFORMANCE INDICATOR, KESEJAHTERAAN DAN MOTIVASI KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PT KEBON AGUNG PABRIK GULA TRANGKIL PATI - Marlinawati, Alina; Violinda, Qristin (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
The problem in this research is the decline in employee morale at PT Kebon Agung Sugar Factory Trangkil Pati. This study aims to determine the effect of performance appraisal based on key performance indicators, welfare and work motivation on employee morale at PT Kebon Agung Trangkil Pati Sugar Factory. This study uses quantitative research methods. The types of data used are primary and secondary data. This research uses probability sampling techniques and simple random sampling techniques. The samples in this study are permanent employees of PT Kebon Agung Trangkil Gula Pati Factory in 2023 with a total of 250 respondents. The measurement of this study used a Likert scale which was then processed using the IMB SPSS Statistics Version 26 analysis tool. Data analysis consisted of validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, F tests, t tests, and coefficient of determination of variables. Key performance indicators have a positive and significant effect on employee morale at PT Kebon Agung Trangkil Pati Sugar Factory, of 33,7% significance value of 0.000. The welfare variable influences employee job satisfaction at PT Kebon Agung Trangkil Pati Sugar Factory, with a significance value of 0.014. The variable of work motivation influences the morale of employees at PT Kebon Agung Trangkil Pati Sugar Factory amounted to a significance of 0.010. The results of this study indicate that simultaneously the key performance indicator variables, welfare and work motivation affect the morale of the employees of PT Kebon Agung Trangkil Pati Sugar Factory, indicating that 34.6% of the variable morale is influenced by key performance indicator variables, welfare and work motivation and 65.4% is influenced by other variables not present in this study.